2019
DOI: 10.1057/s41285-019-00115-y
|View full text |Cite
|
Sign up to set email alerts
|

A wager on the future: a practicable response to HIV pre-exposure prophylaxis (PrEP) and the stubborn fact of process

Abstract: In this article we focus on public health's wager on the social implications of a daily antiretroviral pill to prevent HIV, referred to as PrEP (pre-exposure prophylaxis). The wager is shown to rely on modes of inquiry overly tied to what is known of the present in order to predict the future. Although such inquiry is not unusual when social research is called upon to assist health policy, predictive methodologies are unable to appreciate the dynamic and thus indeterminate nature of process. We ask: what mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The displacement of older ‘safe sex’ norms did not, however, indicate that participants were less invested in community. Many of the PrEP-taking men in this study talked about how other practices related to PrEP such as frequent STI testing and proactive partner notification of diagnoses, advocating for and educating others on PrEP, and participating in research could also be construed as acts of care for partners and community [ 36 ], or a new form of ‘citizenship’.…”
Section: Discussionmentioning
confidence: 99%
“…The displacement of older ‘safe sex’ norms did not, however, indicate that participants were less invested in community. Many of the PrEP-taking men in this study talked about how other practices related to PrEP such as frequent STI testing and proactive partner notification of diagnoses, advocating for and educating others on PrEP, and participating in research could also be construed as acts of care for partners and community [ 36 ], or a new form of ‘citizenship’.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmakon’s dual nature as remedy/toxin reminds us that within medicine’s capacity to save lives remains its ability to poison the (social) body. To question medicine’s shortcomings is not to diminish its positive attributes, but is rather to ask for a more comprehensive view of what biopolitical futures are possible (Rosengarten and Murphy 2019 ).…”
Section: Ambivalence Reflexivity and The Embodied Researcher: Conclmentioning
confidence: 99%
“…Instead, as she puts this, it involved a choice 'to pose the problem [HIV] clearly ' [sic] (Stengers, 1997:216.7). Her account does not detail the immense difficulties faced in making this choice, nor does it mention the inventiveness of cultivating the use of condoms as a protective barrier method for sex, in contrast to a public health insistence on abstinence (Kippax and Race, 2001;Rosengarten and Murphy, 2019). Nevertheless, it dramatizes the importance of a formulation of the HIV problem that is relevant to those who live the response to it.…”
Section: Possibles In the Becoming Of A History Without 'End'mentioning
confidence: 99%
“…In a recent article, Dean Murphy and I have suggested that this early phase of the epidemic can be regarded as the cultivation of a pragmatic response to the problem of HIV. Pragmatic in the sense that foremost in the response was a concern that it should be relevant to living with the given reality or the prospect of such a reality of a communicable infection and, moreover, without presuming to know in advance what would become (Rosengarten and Murphy 2019). By working with what was relevant to those affected by the event of AIDS, this early response to what otherwise seemed as a 'given' problem was effectively altered (Kippax and Stephenson 2012;Kippax and Race 2003).…”
Section: Possibles In the Becoming Of A History Without 'End'mentioning
confidence: 99%